2011
DOI: 10.1017/jfm.2011.450
|View full text |Cite
|
Sign up to set email alerts
|

Effects of body elasticity on stability of underwater locomotion

Abstract: We examine the stability of the "coast" motion of fish, that is to say, the motion of a neutrally buoyant fish at constant speed in a straight line. The forces and moments acting on the fish body are thus perfectly balanced. The fish motion is said to be unstable if a perturbation in the conditions surrounding the fish results in forces and moments that tend to increase the perturbation and it is stable if these emerging forces tend to reduce the perturbation and return the fish to its original state. Stabilit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Note that the three-link swimmer was also used by Jing & Kanso to study the effect of body elasticity on the stability of the coast motion of fish (motion at constant speed). They found that elasticity of the body may lead to passive stabilization of the (otherwise unstable) coast motion, see [8,9]. The present model consisting of a single elliptic body is mostly similar to the system studied by Spagnolie et al (2010) both experimentally and numerically, see [10].…”
Section: Introductionsupporting
confidence: 61%
“…Note that the three-link swimmer was also used by Jing & Kanso to study the effect of body elasticity on the stability of the coast motion of fish (motion at constant speed). They found that elasticity of the body may lead to passive stabilization of the (otherwise unstable) coast motion, see [8,9]. The present model consisting of a single elliptic body is mostly similar to the system studied by Spagnolie et al (2010) both experimentally and numerically, see [10].…”
Section: Introductionsupporting
confidence: 61%
“…wheret andθ r are integration variables. Once θ c (t) is obtained, the position of C can be given by (14),…”
Section: Two-link Model Analysismentioning
confidence: 99%
“…Kanso et al [15] and Melli et al [18] gave a geometric formulation for swimming in a potential flow and calculated optimal strokes. Jing & Kanso [14] used this formulation to study the effects of elasticity and body configuration on the stability of passive locomotion.…”
Section: Introductionmentioning
confidence: 99%
“…where C d is defined as the resistance coefficient of the spoiler cylinder (C d is 1.11, according to the empirical value [34]), and D and L are respectively defined as the diameter and length of the spoiler cylinder. The work of the damping force generated by the spoiler cylinder in a cycle is given by Equation (5):…”
Section: Theoretical Analysismentioning
confidence: 99%
“…The resistance coefficient is a function of the Reynolds number [34]. The Reynolds number is related to the velocity, so the resistance coefficient is related to the speed.…”
Section: Simulation Verification Of the Value Of Resistance Coefficientmentioning
confidence: 99%